2022
DOI: 10.1038/s41467-022-33300-1
|View full text |Cite
|
Sign up to set email alerts
|

Conserved signalling components coordinate epidermal patterning and cuticle deposition in barley

Abstract: Faced with terrestrial threats, land plants seal their aerial surfaces with a lipid-rich cuticle. To breathe, plants interrupt their cuticles with adjustable epidermal pores, called stomata, that regulate gas exchange, and develop other specialised epidermal cells such as defensive hairs. Mechanisms coordinating epidermal features remain poorly understood. Addressing this, we studied two loci whose allelic variation causes both cuticular wax-deficiency and misarranged stomata in barley, identifying the underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 99 publications
1
5
0
Order By: Relevance
“…Cuticle functions in concert with stomata to tightly control water and gas exchange essential for plant photosynthesis and environmental adaptation. Molecular characterization of barley cer-g.10 and cer-s.31 mutants exhibiting wax-deficiency and stomatal misarrangement demonstrated that Cer-g and Cer-s genes respectively encode a YODA-like (YDA) MAPKKK HvYDA1 and a BREVIS-RADIX (BRX) domain protein HvBRX-Solo, two signaling components in stomatal development ( Liu et al., 2022a ). Epidermal phenotype analysis of cer-g.10 , cer-s.31 and cer-g.10 cer-s.31 double mutants revealed that HvYDA1 and HvBRX function in a common pathway to control wax deposition and epidermal patterning ( Liu et al., 2022a ).…”
Section: Regulatory Mechanisms Of Cuticle Biosynthesis In Wheat and B...mentioning
confidence: 99%
See 2 more Smart Citations
“…Cuticle functions in concert with stomata to tightly control water and gas exchange essential for plant photosynthesis and environmental adaptation. Molecular characterization of barley cer-g.10 and cer-s.31 mutants exhibiting wax-deficiency and stomatal misarrangement demonstrated that Cer-g and Cer-s genes respectively encode a YODA-like (YDA) MAPKKK HvYDA1 and a BREVIS-RADIX (BRX) domain protein HvBRX-Solo, two signaling components in stomatal development ( Liu et al., 2022a ). Epidermal phenotype analysis of cer-g.10 , cer-s.31 and cer-g.10 cer-s.31 double mutants revealed that HvYDA1 and HvBRX function in a common pathway to control wax deposition and epidermal patterning ( Liu et al., 2022a ).…”
Section: Regulatory Mechanisms Of Cuticle Biosynthesis In Wheat and B...mentioning
confidence: 99%
“…Molecular characterization of barley cer-g.10 and cer-s.31 mutants exhibiting wax-deficiency and stomatal misarrangement demonstrated that Cer-g and Cer-s genes respectively encode a YODA-like (YDA) MAPKKK HvYDA1 and a BREVIS-RADIX (BRX) domain protein HvBRX-Solo, two signaling components in stomatal development ( Liu et al., 2022a ). Epidermal phenotype analysis of cer-g.10 , cer-s.31 and cer-g.10 cer-s.31 double mutants revealed that HvYDA1 and HvBRX function in a common pathway to control wax deposition and epidermal patterning ( Liu et al., 2022a ). RNA sequencing (RNA-seq) analysis showed that HvYDA1 and HvBRX-Solo coregulate downstream genes associated with cuticle development, epidermal differentiation and patterning, further confirming that HvYDA1-HvBRX-Solo signaling module orchestrates cuticle biosynthesis and epidermal patterning in barley ( Liu et al., 2022a ).…”
Section: Regulatory Mechanisms Of Cuticle Biosynthesis In Wheat and B...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to complementation analysis, there are 79 different cer genomic loci in barley [ 2 ]. Despite many known cer mutants, only a few genes associated with these mutations have been identified thus far [ 3 , 4 ]. Among them is the Cer-cqu gene cluster known for leaf sheath wax accumulation control [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…CER‐ZH was identified as HvKCS1 , required for fatty acid elongation (Li et al ., 2018). Recently, the HvSHINE1 transcription factor involved in the regulation of wax biosynthesis was found to be encoded by CER‐X (McAllister et al ., 2022), while CER‐G and CER‐S were characterized as encoding two additional transcription factors, HvYDA1 and HvBRX‐Solo , regulating both cuticular integrity and cell patterning (Liu et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%